Moopa or barren: A rereading of the 1840 English–Setswana gospel of Luke 1:36–38 from a Setswana traditional practice - Mothoagae, Itumeleng D. (HTS teologiese studies, 2019)
The 1840 gospel of Luke as translated by Moffat presents us with the cultural and imperial surveillance performed by a patriarchal system through the institutionalisation of motherhood and womanhood (bosadi). Motherhood or womanhood (bosadi) as a patriarchal institution has been a space in which patriarchal discursive practices have been realised through an act of politicising motherhood or womanhood. At the centre of this act of politicisation of motherhood or womanhood (bosadi) is the ability to carry and bear children (pelegi). The institution of motherhood or womanhood has facilitated a binary between motherhood (bosadi) and bareness (moopa). The womb/popelo as a symbol of fertility becomes the space of mothering women, of labelling, categorising and naming women that the system locates as moopa or barren. The article seeks to reread the narrative on childbearing in the 1840 gospel of Luke from a decolonial framework. I will argue that childbearing, as a patriarchal institution, has been a space in which the gaze of patriarchy has been produced to subjugate women through cultural and imperial masculinist gaze. I will also argue that there is a need to decolonise and liberate such a space (womb) as not a determinant of motherhood.